1993
DOI: 10.1093/bja/71.4.540
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl Inhibits the Uptake of [ 3 H]noradrenaline in Cultured Neuronal Cells

Abstract: We have examined how fentanyl modulates [3H]noradrenaline uptake in two cultured neuronal cell preparations, the human neuroblastoma SH-SY5Y and the rat phaeochromocytoma PC12. Fentanyl produced a significant, dose-dependent inhibition of [3H]noradrenaline uptake at concentrations in excess of 0.1 mumol litre-1 (P < 0.05) and 0.3 mumol litre-1 (P < 0.05) for PC12 and SH-SY5Y cells, respectively. However, these values exceed the serum concentration of fentanyl required to produce analgesia. At the maximum conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Both tyrosine hydroxylase and dopamine-p-hydroxylase activities have been reported (Ross et al, 1983;Ross & Biedler, 1985) and these cells express muscarinic M3 receptors (Lambert et al, 1989), M2-adrenoceptors (Kazmi & Mishra, 1989) and ,p and 6 opioid receptors (Kasmi & Mishra, 1987). In a previous study we have shown that SH-SY5Y cells take up substantial amounts of [3H]-noradrenaline with a t4 of 5.7min (Atcheson et al, 1993b). Scott and colleagues (1986) demonstrated (in differentiated cells) that both K+ (50 mM) depolarization and acetylcholine (100 pLM) evoked a modest monophasic increase in the release of [3H]-noradrenaline; these data are confirmed and extended in this manuscript.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Both tyrosine hydroxylase and dopamine-p-hydroxylase activities have been reported (Ross et al, 1983;Ross & Biedler, 1985) and these cells express muscarinic M3 receptors (Lambert et al, 1989), M2-adrenoceptors (Kazmi & Mishra, 1989) and ,p and 6 opioid receptors (Kasmi & Mishra, 1987). In a previous study we have shown that SH-SY5Y cells take up substantial amounts of [3H]-noradrenaline with a t4 of 5.7min (Atcheson et al, 1993b). Scott and colleagues (1986) demonstrated (in differentiated cells) that both K+ (50 mM) depolarization and acetylcholine (100 pLM) evoked a modest monophasic increase in the release of [3H]-noradrenaline; these data are confirmed and extended in this manuscript.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Seward et al (1991) demonstrated that opiate receptor occupancy in these cells closed VSCC. To address these discrepancies we have examined the roles played by intracel- Atcheson et al (1993b). Gross morphological examination showed no evidence of differentiation as a result of the experimental manipulations reported here.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…As previously described, fentanyl differs from morphine since the former has considerably increased lipid solubility, greater selectivity for m-opioid receptors over k and d, but has similar binding affinity as morphine on m-opioid receptors. In addition, fentanyl, but not morphine, is capable of acting as a norepinephrine reuptake inhibitor (Mather, 1983;Atcheson et al, 1993). High-dose fentanyl (e.g., 1-100 mM) blocks reuptake of [ 3 H]norepinephrine into human neuroblastoma and rat pheochromocytoma cells (Atcheson et al, 1993).…”
Section: Neurochemistry and Neuroanatomy In Wcsmentioning
confidence: 99%